Brain TRPV1 channel-mediated calcium influx: the immunomodulatory pathway of acupuncture in neuroinflammation - Tang, Qingqing; He, Min; Zheng, Peng; Sun, Mengmeng; Cao, Jiazhen; Zhang, Qi; He, Jing; Sun, Run; Zhu, Bing; Li, Tie (Frontiers in Immunology, 2025)
Neuroinflammation represents the central pathological process in neurological disorders. Effectively regulating neuroinflammation to restore immune homeostasis and alleviate neuronal damage has emerged as a critical strategy in the prevention and treatment of these diseases. In recent years, the role of acupuncture in neuroimmune regulation, along with its anti-inflammatory and analgesic effects, has attracted considerable attention. Its potential to modulate immune homeostasis and inflammatory responses through various targets and pathways has been gradually elucidated, offering new research directions for the regulation of neuroinflammation. A series of studies have emphasized that acupuncture has significant clinical applications by regulating the immunoinflammatory pathway mediated by the brain’s TRPV1 channel. This discovery not only enhances the scientific understanding of the mechanisms underlying acupuncture but also offers new potential targets for the prevention and treatment of neuroinflammation-related diseases. The immunomodulatory properties of brain TRPV1 channels in inflammation associated with the nervous system have been emphasized. Furthermore, this study explores the immunomodulatory benefits of acupuncture in treating neuroinflammation, focusing on the potential mechanisms of TRPV1 channels at the brain level, as well as the criteria for selecting acupoints, intensity, frequency, and other relevant parameters in these studies. A deeper understanding of the neuroimmune regulatory mechanisms mediated by brain TRPV1 channels may offer new strategies and approaches for developing treatments or preventing neuropathological diseases.